Influence of pranayama on breath holding capacity and reaction time of junior state level elite swimmers - Tusharkanti Bera; Kanchan Chourasia; Sanjay Uddhav Shete; Anita Verma (Wolters Kluwer Medknow Publications, 2017)
Introduction: Sport like swimming requires maximum accuracy in style, fitness, skill and training. Moreover, the swimmers must possess a better reaction time as well as breath holding capacity that saves time for exhibiting best performance. Objective: It is thought that regular practice of kumbhaka phase of pranayama may improve swimmers' breath holding capacity and reaction time. Since literature is silent about this concept, the present investigation was carried out. Method: Thirty male state level swimmers (n = 30), age: 16-18 years, volunteered in this study. This experiment considered a single group design, where all the selected subjects were assessed for two variables viz., reaction time and breath holding capacity at the baseline (i.e., 1st test or pre-test). Further, after a 6-week of swimming practice (1½ hours daily in the afternoon), the variables were re-tested (i.e., 2nd test or mid-test). After the 2nd test was over, all the subjects underwent 6 weeks of combined practice (i.e., swimming followed by pranayama) for 1½ hours daily in the morning. Finally, the subjects were assessed for the selected variables (i.e., 3rd test or posttest). Statistical Analysis: Repeated measures ANOVA followed by Newman-Kuels post hoc test was employed to record influence of pranayama practices on the variables. Results: The results revealed that swimming plus pranayama training leads to significant increase in breath holding capacity whereas reduction in reaction time. Conclusion: Pranayama practice leads to significant improvement in breath holding capacity and reaction time of swimmers.